2007
DOI: 10.5688/aj710584
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Diabetes Certificate Program on PharmD Students' Knowledge and Skills

Abstract: Objectives. To determine the impact of a pregraduation diabetes certificate program on PharmD students' knowledge and skills. Methods. A comprehensive elective in diabetes was created and implemented in the third-professional year of the PharmD curriculum. A nonrandomized, single-blinded, controlled, 2-year study was conducted to determine the impact of the elective. Written and oral examinations were administered to the participants and students in a control group. Results. The certificate students' (N 5 25) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Limited studies have reported that a nontraditional diabetes curriculum can benefit pharmacy students. [8][9][10] These complex programs involving role-playing as a patient with diabetes have demonstrated positive effects. Only 1 other study has published findings specific to a living with diabetes simulation/role-playing experience; however, this was using a type 1 diabetes regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies have reported that a nontraditional diabetes curriculum can benefit pharmacy students. [8][9][10] These complex programs involving role-playing as a patient with diabetes have demonstrated positive effects. Only 1 other study has published findings specific to a living with diabetes simulation/role-playing experience; however, this was using a type 1 diabetes regimen.…”
Section: Discussionmentioning
confidence: 99%
“…7 Implementation of nontraditional diabetes curriculum using active learning and practice-based exercises improved pharmacy students' knowledge and skills in the management of diabetes. [8][9][10] Most of the published literature highlights advanced diabetes care courses and training and certificate programs. These programs incorporated a diabetes simulation into their program, but they did not evaluate the impact of the simulation alone.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Attempts to enhance students' skills and depth of knowledge by offering focused concentrations also have been described in the literature. [7][8][9][10] The Southern Illinois University Edwardsville (SIUE) School of Pharmacy has developed an education concentration for PharmD students to address faculty recruitment and retention. The concentration requires that more than 50% of a student's didactic electives, ie, 6 or more of the 11 didactic elective credits and 1 advanced pharmacy practice experience (APPE) focus on a specialized track.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a diabetes certification program, pharmacy students were required to complete a personal diet analysis as well as role-play for 1 week as a person with diabetes. 3 Two other schools implemented an activity that used the Patient Empathy Modeling method and required students to simulate the life of a patient who was living with multiple chronic diseases and experiencing economic, cultural, and/or communication challenges to obtaining care. 4 In another study, medical students were voluntarily admitted to a hospital overnight in order to understand what a hospitalized patient experiences.…”
Section: Introductionmentioning
confidence: 99%